2022
DOI: 10.3390/molecules27030851
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Thermophysical Properties of Ammonium-Based Protic Ionic Liquids and Their Potential Ability towards CO2 Capture

Abstract: Ionic liquids, which are extensively known as low-melting-point salts, have received significant attention as the promising solvent for CO2 capture. This work presents the synthesis, thermophysical properties and the CO2 absorption of a series of ammonium cations coupled with carboxylate anions producing ammonium-based protic ionic liquids (PILs), namely 2-ethylhexylammonium pentanoate ([EHA][C5]), 2-ethylhexylammonium hexanoate ([EHA][C6]), 2-ethylhexylammonium heptanoate ([EHA][C7]), bis-(2-ethylhexyl)ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…After the absorption, [MOBMIM][His] and [MOBMIM][Gly] stayed in the liquid phase, while [MOBMIM][Arg] and [MOBMIM][Gly] turned to gel. Recently, Zailani et al (2022) synthesized ammonium based protic ILs using 2-ethylhexylammonium and bis-(2-ethylhexyl) ammonium coupled with pentanoate, hexanoate, and heptanoate ([EHA][C 5 ], [EHA][C 6 ], [EHA][C 7 ], [BEHA][C 5 ], [BEHA][C 6 ], and [BEHA][C 7 ]). The absorption capacity (mol/kg) decreased in the order of [C 5 ] < [C 6 ] < [C 7 ], and [EHA][C 7 ] showed the highest absorption capacity (∼3.0 mol/kg at 29 bar and room temperature).…”
Section: Literature Survey Data Collection Properties Perdition and I...mentioning
confidence: 99%
“…After the absorption, [MOBMIM][His] and [MOBMIM][Gly] stayed in the liquid phase, while [MOBMIM][Arg] and [MOBMIM][Gly] turned to gel. Recently, Zailani et al (2022) synthesized ammonium based protic ILs using 2-ethylhexylammonium and bis-(2-ethylhexyl) ammonium coupled with pentanoate, hexanoate, and heptanoate ([EHA][C 5 ], [EHA][C 6 ], [EHA][C 7 ], [BEHA][C 5 ], [BEHA][C 6 ], and [BEHA][C 7 ]). The absorption capacity (mol/kg) decreased in the order of [C 5 ] < [C 6 ] < [C 7 ], and [EHA][C 7 ] showed the highest absorption capacity (∼3.0 mol/kg at 29 bar and room temperature).…”
Section: Literature Survey Data Collection Properties Perdition and I...mentioning
confidence: 99%
“…72 In general, an increase of approximately 90 1C or 150 1C in decomposition temperatures is observed for the phosphonium carboxylate ILs (carboxylate anions with linear alkyl chains) compared to their equivalent imidazolium or ammonium counterparts, respectively. 73 When the carboxylate anions are derived from amino acids, the corresponding phosphonium ILs show a lower thermal stability. 74 As expected, shorter alkyl side-chains in the phosphonium cations lead, in general, to higher decomposition temperatures.…”
Section: Thermal Analysismentioning
confidence: 99%
“…As a comprehensive study, Zailani et al [ 7 ] reported the results of their research on the synthesis of a series of ammonium cations coupled with carboxylate anions producing ammonium-based protic ionic liquids, and their densities, viscosities, refractive indices, thermal decomposition temperatures, glass temperatures, and CO 2 absorption was also reported.…”
Section: Contributionsmentioning
confidence: 99%